Arteriovenous malformation of the oral cavity: A case report - Muneera Almedaires; Alhanouf Albarrak; Bayan Alshuhail; Faraz Mohammed (Elsevier, 2019)
Aim: The aim of the case report is to discuss the clinical, histological features, differential diagnosis, treatment and follow up the case. Case presentation: Vascular malformations are defined as congenital lesions that become apparent later in life, formed by dysplastic vascular channels, with no endothelial proliferation or involution, that grow possibly due to hemodynamic mechanisms. It can be further subdivided into venous, capillary, arteriovenous and lymphatic malformations.A 54 yrs old housewife female patient reported to the dental clinics with a swelling in buccal mucosa near the left commissure of 5 years duration. Differential diagnosis:• Mucocele• Hemangioma• Vascular malformation• Mucoepidermoid carcinom Investigation: The lesion was blanched on compression with diascopy.Histological sections confirmed the diagnosis of arteriovenous malformation.Follow up was done till 6 months. Conclusion: This case demonstrates AVM of the left buccal mucosa. Although rare, clinicians should be aware of their potentially life threatening complications. This can be avoided by early detection and intervention, with adequate follow up to monitor recurrence.